1993
DOI: 10.1109/86.285733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the periacetabular osteotomy on the stress on the human hip joint articular surface

Abstract: Long-lasting over-elevated stress on the hip joint articular surface can damage the articular cartilage and is connected with arthrosis development. Periacetabular pelvic osteotomy is performed in order to prevent arthrosis development in different cases of residual hip dysplasia where the stress on the hip joint articular surface is increased because of inadequate femoral head coverage, i.e., too small hip joint weight bearing area. The aim of this work is to estimate a decrease of the stress on the hip joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 9 publications
2
34
0
Order By: Relevance
“…Accordingly, the magnitude of the resultant hip force increased in all stratification groups, which is consistent with theoretical predictions of the relationship between the center of rotation and the resultant hip force (Figure). Our clinical results have thus confirmed theoretical predictions (Iglič et al 1993b) that the resultant hip force itself is not an adequate biomechanical parameter for preoperative planning, and that rotational osteotomy can effectively reduce the contact hip stress although the resultant hip force may be slightly increased.…”
Section: Discussionsupporting
confidence: 74%
“…Accordingly, the magnitude of the resultant hip force increased in all stratification groups, which is consistent with theoretical predictions of the relationship between the center of rotation and the resultant hip force (Figure). Our clinical results have thus confirmed theoretical predictions (Iglič et al 1993b) that the resultant hip force itself is not an adequate biomechanical parameter for preoperative planning, and that rotational osteotomy can effectively reduce the contact hip stress although the resultant hip force may be slightly increased.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies found that in dysplastic conditions where ϑCE is small or negative, hip joint contact stress is higher than in hips with a larger ϑCE; however, stress can also be higher due to a higher or a too vertical resultant hip joint force (Iglič et al,1993a;Ipavec et al,1999;Genda et al,2001). The direction and magnitude of the resultant hip joint force R depends, among other factors, on the femoral and pelvic geometry (Brand , 1997;Iglič et al,1993b).…”
Section: Preoperative Planningmentioning
confidence: 99%
“…In order to solve Eq. (11), the ordinary spherical coordinate system was used in the previous papers (Iglič et al, 1993;Ipavec et al, 1999). Classical spherical coordinates lead to the complex expression for the boundaries of the weight-bearing area.…”
Section: Equilibrium Equationsmentioning
confidence: 99%
“…In the rotated coordinate system the pole of stress P as well as force R lie in the y ′ a = 0 plane. For a force in y ′ a = 0 plane, method for determination of the position of the stress pole which was developed for the one-leg standing with the force in the frontal plane and acetabulum symmetrical with respect to this plane (Herman et al, 2002;Iglič et al, 1993;2002) can be used. In order to solve Eq.…”
Section: Equilibrium Equationsmentioning
confidence: 99%